Hydra Mesoglea Proteome Identifies Thrombospondin as a Conserved Component Active in Head Organizer Restriction - Lommel, Mark; Strompen, Jennifer; Hellewell, Andrew L.; Balasubramanian, Gnana Prakash; Christofidou, Elena D.; Thomson, Andrew R.; Boyle, Aimee L.; Woolfson, Derek N.; Puglisi, Kane; Hartl, Markus; Holstein, Thomas W.; Adams, Josephine C.; et al. (Scientific reports, 2018)
Thrombospondins (TSPs) are multidomain glycoproteins with complex matricellular functions in tissue homeostasis and remodeling. We describe a novel role of TSP as a Wnt signaling target in the basal eumetazoan Hydra . Proteome analysis identified Hydra magnipapillata TSP (HmTSP) as a major component of the cnidarian mesoglea. In general, the domain organization of cnidarian TSPs is related to the pentameric TSPs of bilaterians, and in phylogenetic analyses cnidarian TSPs formed a separate clade of high sequence diversity. HmTSP expression in polyps was restricted to the hypostomal tip and tentacle bases that harbor Wnt-regulated organizer tissues. In the hypostome, HmTSP- and Wnt3 -expressing cells were identical or in close vicinity to each other, and regions of ectopic tentacle formation induced by pharmacological β-Catenin activation (Alsterpaullone) corresponded to foci of HmTSP expression. Chromatin immunoprecipitation (ChIP) confirmed binding of Hydra TCF to conserved elements in the HmTSP promotor region. Accordingly, β-Catenin knockdown by siRNAs reduced normal HmTSP expression at the head organizer. In contrast, knockdown of HmTSP expression led to increased numbers of ectopic organizers in Alsterpaullone-treated animals, indicating a negative regulatory function. Our data suggest an unexpected role for HmTSP as a feedback inhibitor of Wnt signaling during Hydra body axis patterning and maintenance.